Silver Nanowires Network Film with Enhanced Crystallinity toward Mechano‐Electrically Sustainable Flexible‐Electrode. Issue 1 (30th November 2020) - Kim, Mi‐Jeong; Ko, Dong‐Su; Kim, Jung‐Hwa; Cho, Eun‐Hyoung; Yang, Dae Jin; Kwak, Chan; Sohn, Hiesang
Abstract: This report presents the improved mechano‐electric sustainability of Ag NWs network with enhanced crystallinity (c‐Ag NW) based on the systematic bending‐fatigue study of Ag NWs network and its application toward electronic device built on patterned electrode. First, the mechano‐electric stability of Ag NWs network film is found to be highly associated with their crystalline structural deformation, i.e., defects or dislocation density by externally applied strains. Based on this result, c‐Ag NWs are prepared by the solution based thermal annealing at 70 ° C and integrated into c‐Ag NWs network film. By analyzing crystalline structures and nano‐morphologies, as‐formed c‐Ag NW network film exhibits enhanced crystallinity and reduced dislocation density. In the bending fatigue tests under application of strain (6.7%, bending radius: 1 mm) during the 200 000 cycles, c‐Ag NWs network film shows highly reduced (> 500%) resistance change (Δ R /Δ R o : 45%) than that of pristine Ag NW network film (Δ R /Δ R o : 241%). In the application of c‐Ag NW network toward patterned electrode, the electrode demonstrates the comparable electrical property (9.41 kΩ ) to that of ITO based one (8.01 kΩ ) despite the reduced number of nanowires in 6 µ m neck diamond electrode pattern. Abstract : The crystallized Ag nanowires film (c‐Ag NWs) are prepared through solution annealing (70 °C) for the flexible electronic device. c‐Ag NWs film shows the excellent mechano‐electric stability (resistance change, Δ R /Δ R o : 45%) after 200 000 bending cycles under strain of 6.7%. In addition, c‐Ag NWs based patterned electrode demonstrates the comparable electrical property (9.41 kΩ) to that of ITO‐based one (8.01 kΩ).